The Implementation of Holistic Integrative Program In Early Childhood Education In East Java - Wahono Wahono; R. Panji Hermoyo (PROCEEDING UMSURABAYA, 2020)
Abstract. This study aims to obtain information about the implementation of HolisticIntegrative Program developed in Early Childhood Education. This program is moremeaningful if the environment around the children can be used as the basis for development. This study used a descriptive qualitative approach. This research involved educators in Early Childhood Education in East Java Province. The data were analyzed using descriptive analysis. The objectives of this study were as follows: (1) to describe the services of holistic integrative program in early childhood education, (2) to describe the understanding and process of holistic integrative services, (3)to describe Holistic Integrative Program in Early Childhood Education. Therefore, it can be concluded that: (1) The children have the right to avoid disease and get the adequate nutrition to explore and develop their brainpower maximally; (2) Food can be used as a medium to educate children to be able to receive, like choosing good food and determining the amount of adequate and qualifiedfood; (3) Human rights are the basic rights carried from birth which are universally applicable to all humans.